Democratic Republic of the Congo : 2007 Article IV Consultation; Staff Report; Staff Supplement; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Democratic Republic of the Congo. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This 2007 Article IV Consultation highlights that the Democratic Republic of the Congo (DRC) has made significant economic and political progress since 2001, after years of conflict and political instability. Adoption of prudent macroeconomic policies resulted in rapid disinflation and the stabilization of the exchange rate. The implementation of structural reforms made the economy more open, removed major price distortions, and strengthened macroeconomic policy management. Executive Directors have encouraged the new government to work with all parties to improve security and bring peace to all country provinces.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet